Implementasi Aplikasi Sistem Informasi Pemerintah Daerah Terhadap Peningkatan Kualitas Pengelolaan Keuangan Daerah Pada Pemerintah Provinsi Riau - Annisa, Annisa (Universitas Pahlawan Tuanku Tambusai, 2025)
Regional financial management is a crucial aspect of good governance. Effective management of regional finances significantly impacts regional development, public welfare, and the strengthening of local democracy. Therefore, regional financial management must be supported by reliable information technology. Since the 2023 fiscal year, the Riau Provincial Government has fully implemented the SIPD (Sistem Informasi Pemerintahan Daerah) application as its financial management system. This application, developed by the Ministry of Home Affairs, is designed to be the sole platform used by all local governments in Indonesia for financial management. This study examines the readiness of the Riau Provincial Government to adopt the SIPD application and its impact on the quality of regional financial management. The research applies the “A Model of Policy Implementation” theory, using a qualitative approach and triangulation as the data collection technique. The findings indicate that the Riau Provincial Government is highly prepared to implement the SIPD application in its financial management processes. Moreover, the SIPD application has contributed to an improvement in the quality of financial management in the region, as reflected by the increase in the Regional Financial Management Index (IPKD) of Riau Province to 82.923 after adopting the application. Keywords: Financial Management, Local Government, Information System